INFLUENCE OF EMPLOYEESʼ SCIENTIFIC ELA-BORATIONS OF DEPARTMENT OF THERAPEUTIC DENTISTRY FOR INDICATORS OF MEDICAL WORK - Petrushanko, T.A.; Litovchenko, I.Yu.; Nikolishin, A.K.; Kotelevskaya, N.V.; Sidash, Yu.V. (World of Medicine and Biology, 2014)
The article presents an analysis of quantitative and qualitative indicators of medical staff of the department of therapeutic dentistry, which indicates an increase in the efficiency of the therapeutic processis as a result of active introduction into practice of scientific development of new technologies proposed by scientists of the department.
Keywords: performance dentist therapist; complication of tooth decay; treatment